(untitled) (Journal of Psychiatrists’ Association of Nepal, 2026)
Background: Internet use is an integral part of daily living in current world; however, its misuse is likely to cause addiction and have negative impact in mental health. Internet use disorder (IUD) has been studied worldwide, however there are limited research on its prevalence and psychiatric co-relation among youth psychiatric patients in Nepal. Objectives: To determine the prevalence of internet use disorder, find out its association with psychiatric co-morbidities, and describe socio-demographic characteristics among youth psychiatric out-patients in eastern Nepal. Methods and materials: A cross-sectional study was conducted in psychiatry out-patient department of a tertiary care teaching hospital in eastern Nepal from January 2021 to January 2022. Total of 146 consenting youth patients aged 15-24 years were enrolled using consecutive sampling method. Young’s Internet Addiction Test (YIAT) was administered to access IUD. Psychiatric diagnosis was made by a consultant psychiatrist using ICD-10/DCR criteria and data were analyzed using descriptive statistics and chi square tests at 95% confidence intervals. Result: Among the 146 participants (80 male, 66 female; mean age was 19.99 ± 2.87 years), 89.7% of youth patients were internet users. The prevalence of internet use disorder was found in 33.6% (mild: 34.2%, moderate: 30.8% and severe: 2.7%). Higher level of internet use disorder was significantly associated with middle & high socioeconomic status, urban residence and single marital status. In psychiatric diagnosis; Anxiety (43.7%), substance use disorder (37.5%) and Depressive disorder (34.0%) showed higher but statistically insignificant association with internet use disorder. Conclusion: Internet use disorder is found in 1/3rd youth psychiatric out-patients in Nepal, particularly among middle and high socio-economic status, urban residing population and single patients. These findings highlight the need for screening for IUD in psychiatric settings and intervene the youth psychiatric patients with its risk. Abbreviations: ADHD- Attention Deficit Hyperactive Disorder, CIUS- Compulsive internet use scale, CIU- Compulsive internet User, DCR- Diagnostic Criteria for research, DSM- Diagnostic and Statistical Manual of Mental disorders, IAT- Internet Addiction test, IUD- Internet Use Disorder, ICD-10- International Classification of diseases, 10th revision, IRC- Institute ethical review board and committee, NIU- Normal internet user, OPD- Out-patient Department, PIU- Problematic Internet User, WHO- World Health Organization, YIAT- Young’s Internet Addiction Test